2006
DOI: 10.1002/jobm.200510006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a biphenyl-utilizing psychrotrophic bacterium,Hydrogenophaga taeniospiralis IA3-A, that cometabolize dichlorobiphenyls and polychlorinated biphenyl congeners in Aroclor 1221

Abstract: A psychrotrophic bacterium isolated from polychlorinated biphenyls (PCBs)-contaminated soil grew on biphenyl as sole carbon and energy source, and actively cometabolized PCBs at low temperature. Analysis of cellular fatty acids indicate that the bacterium is most closely related to Hydrogenophaga taeniospiralis. Resting cells incubated with 10 ppm of Aroclor 1221 at 5 or 30 degrees C for 48 h removed all mono-, most di-, and several trichlorobiphenyls. At 5 degrees C, removal of MCBs (monochlorobiphenyls) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…The 16S rRNA gene clone libraries and T-RF intensities for this time point might indicate the dominant role of Hydrogenophaga in the biphenyl metabolism in the horseradish rhizosphere (Table 1). In recent studies of Lambo and Patel (13)(14)(15), a member of Hydrogenophaga was characterized as a psychrotolerant biphenyl-utilizing bacterium that is able to cometabolize several mono-, di-, and trichlorobiphenyls at low temperatures and also a tetrachlorobiphenyl isomer at 30°C. Thus, this bacterium was put forward as an organism that could be useful for the bioremediation of PCBs in colder climates.…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA gene clone libraries and T-RF intensities for this time point might indicate the dominant role of Hydrogenophaga in the biphenyl metabolism in the horseradish rhizosphere (Table 1). In recent studies of Lambo and Patel (13)(14)(15), a member of Hydrogenophaga was characterized as a psychrotolerant biphenyl-utilizing bacterium that is able to cometabolize several mono-, di-, and trichlorobiphenyls at low temperatures and also a tetrachlorobiphenyl isomer at 30°C. Thus, this bacterium was put forward as an organism that could be useful for the bioremediation of PCBs in colder climates.…”
Section: Discussionmentioning
confidence: 99%
“…3), the authors suggested that it would be more effective in the aerobic phase of a two-phase bioremediation process, where highly chlorinated congeners would be first dechlorinated in an anaerobic phase. The same authors detected dissimilar removal of congeners in Aroclor 1221 at 5 C and 30 C and found that the temperature also influenced specificity of cells for some contaminants (Lambo and Patel, 2006a). However, on the basis of the degree of PCB removal at 5 C and 30 C, the authors suggested Pathway for bacterial aerobic degradation of g-hexachlorocyclohexane.…”
Section: G-hexachlorocyclohexanementioning
confidence: 82%
“…isolated from a lake in Antarctica (Peeters et al, unpublished sequence, NCBI). Other closely related Hydrogenophaga species have been reported to be capable of benzene and chlorinated biphenyl degradation [50]. A close relative to another potent chlorinated organic compound-degrader was Achromobacter sp.…”
Section: Discussionmentioning
confidence: 99%